Journal of Atmospheric Chemistry - Journal of Atmospheric Chemistry (Springer Nature, 2026)
The Journal of Atmospheric Chemistry is devoted to the study of the chemistry of the Earth's atmosphere, the emphasis being laid on the region below about 50 km. The strongly interdisciplinary nature of atmospheric chemistry means that it embraces a great variety of sciences, but the journal concentrates on the following topics: Observational, interpretative and modelling studies of the composition of air and precipitation and the physiochemical processes in the Earth's atmosphere, excluding air pollution problems of local importance only. The role of the atmosphere in biogeochemical cycles; the chemical interaction of the oceans, land surface and biosphere with the atmosphere. Laboratory studies of the mechanics in homogeneous and heterogeneous transformation processes in the atmosphere. Descriptions of major advances in instrumentation developed for the measurement of atmospheric composition and chemical properties.
FI 0.55
Q2
Keywords: Earth; Space & Environmental Sciences; Atmospheric Sciences; Ciencias atmosféricas; Acuerdos transformativos; Transformative agreements; Química de la atmósfera terrestre y composición del aire; Ciclos biogeoquímicos e interacciones atmósfera‑océano‑suelo‑biosfera; Procesos químicos atmosféricos, transformación homogénea/heterogénea e instrumentación para medir la composición